The medicinal use of Carapa guianensis Abul. (Andiroba) (Research, Society and Development, 2021)
Objectives: The general objective is to identify the medicinal properties of Carapa guianensis Aubl by the Amazon population. Methodology: This is a literature review in online databases of books, theses, dissertations, and articles published between 2015 and 2021. It was identified in the research that the Andiroba lipid extract, obtained from almonds where it is traditionally used by people Amazon due to its anti-inflammatory properties, such as soothing muscle and joint pain, disinfecting or healing the skin because of insect bites or to tone the hair and scare away lice. Conclusion: Carapa guianensis Aubl has proven therapeutic effects both by popular culture and by scientific studies, and can be used as healing, antiparasitic, antifungal and bactericidal and cosmetics.